Implementation of Performance-Based Accounting on Good Financial Governance in Local Governments in Papua Province - Waromi, Juliana; Rofingatun, Siti; Karubaba, Jois Kristin (Amkop Management Accounting Review (AMAR), 2025)
Improving transparency and accountability in public financial management is essential to realising good governance. Local governments are required to implement an accounting system that not only records financial transactions but also measures performance and results achieved. This study aims to analyse the effect of Performance-Based Accounting Implementation on Good Financial Governance in local governments in Papua Province. This is a quantitative study employing a survey approach, utilizing a closed-ended questionnaire as the research instrument. The research population comprises all financial management officials in the Papua local government, selected through purposive sampling, with a sample of 200 respondents who meet the criteria for direct involvement in planning, budgeting, reporting, and the evaluation of financial performance. The data were analysed using Partial Least Squares–Structural Equation Modelling (PLS-SEM) in SmartPLS. The results showed that implementing performance-based accounting had a positive and significant effect on good financial governance. This indicates that the more optimal the implementation of the performance-based accounting system, the better the transparency, accountability, effectiveness, efficiency, and legal compliance in regional financial management. This finding reinforces the New Public Management (NPM) approach, which emphasises efficiency, effectiveness, transparency, and accountability in the public sector. This approach forms the basis for implementing a results-based accounting system. In addition, these findings have practical implications for local governments, strengthening the capacity of their apparatus and results-based reporting systems to achieve sustainable good financial governance.